The Impact of Colonial Land Tenure Policies on the Gusii People in Kenya - Lameck Okerosi Atika; Onjala Isaias; Fredrick Z. A. Odede; Wallace Atambo (European Scientific Journal, ESJ, 2019)
Different scholars have looked at the general economic impacts of the land reforms and legal implications at national level. However, a few studies have been done on economic history in Gusiiland. This study aimed at analyzing the impact of the colonial land tenure reforms on the Abagusii customary land tenure practices in Gusii, Kenya. This study used the articulation of modes of production theory to analyze the effects of land reforms on the Abagusii community from 1895 to 1963. Descriptive Survey Design was used to guide the study.Purposive and snowball sampling methods was instrumental in selected the respondents with a sample size of 61 informants. The primary sources of data were obtained from the archives, field interviews, observation and focus group discussions while secondary data was obtained from written sources like books, Journals, magazines, periodicals, Newspaper Articles, unpublished theses, seminar papers, and electronically stored information on the internet. Logical historical method was employed in the actual process of analyzing and interpreting the data gathered.The study established that land consolidation and the issuance of individual land owners with title deeds has increased land conflicts, land titling and issuance of individual titles has increased land speculation, and land tenure reforms have failed to solve land problems or improve the agricultural sector, as well as, failing to change the African mind set or behavior of the smallholder farmers in Gusii, Kenya.